Uji Aktivitas Antihiperglikemia Ekstrak Etanol Daun Delima Putih (Punica granatum L.) pada Mencit Jantan (Mus musculus L.) yang Diinduksi Aloksan - Pangesti, Clara; Nopiyanti, Vivin; Hayu Widyasti, Jena (Jurnal Farmasi (Journal of Pharmacy), 2021)
Pomegranate leaves (Punica granatum L.) contain flavonoids as a decrease in blood glucose levels and prevent tissue damage due to oxidative stress. This study aims to determine the effect of white pomegranate leaf ethanol extract on blood glucose levels, body weight, and the effective dose of white pomegranate leaf ethanol extract in reducing blood glucose levels in mice induced by alloxan. A total of 30 male mice were divided into 6 treatment groups, namely group I (normal), group II (negative control of CMC-Na 0.5%), group III (positive control of glibenclamide), group IV (extract 140 mg/Kg BW), group V (extract 280 mg/Kg BW) and group VI (extract 560 mg/Kg BW). The treatment was given for 14 days by measuring blood glucose levels and body weight on days 0, 3,10, and 17. The results of the analysis of blood glucose levels and body weight were carried out statistically through the Multivariate Test and Tukey Post Hoc test, while the decrease in glucose levels analyzed using One-Way Anova test and Tukey Post Hoc test. The results showed that the extract had antihyperglycemic activity in alloxan-induced mice. The ethanol extract of white pomegranate leaves at a dose of 280 mg/Kg BW had an effective antihyperglycemic activity compared to doses of 140 mg/Kg BW and 560 mg/Kg BW which were comparable to the positive control group.